Hidden scars: the impact of violence and the COVID-19 pandemic on children's mental health - Najat Maalla M'jid (BMC, 2020)
Abstract More than 1 billion children are exposed to violence every year. The devastating immediate and long-term impact of violence on the mental health of children is well established. Despite commitments made by the international community to end violence against children and support their mental health, there has been a serious lack of investment and capacity to provide quality, rights-based, culturally appropriate mental health care globally. The arrival of the COVID-19 pandemic has magnified these challenges. This article outlines how the risk of children experiencing violence has increased and how the pandemic has weakened the capacity of child protection and mental health services to respond. The article argues for child protection, mental health and other core services to be prioritized during and after the pandemic. A failure to do so will undermine the international community's ability to achieve the Sustainable Development Goals by 2030 and to fulfil its obligations under the UN Convention on the Rights of the Child.